Philosophy of education in China: origins and main stages - Zheng Ren (Journal of the Belarusian State University. Philosophy and Psychology, 2022)
In the article sources of the origin of the philosophy of education in China are designated (traditional Chinese philosophy, Western philosophy of education, the theory of Marxism), which differ in the subject field, categorical apparatus, used theoretical approaches. The further development of the philosophy of education in China is characterised by the dominance of one of these approaches or their synthesis. The stages of development of the philosophy of education as academic disciplines and areas of research in China are described – the stage of formation and development (1920–30s), the decline of the philosophy of education in China (1937 – 1970s), the revival of the philosophy of education (1970–90s), the stage of modern development of the philosophy of education (the end of the 20th century – the present time), which are characterised by socio-political contexts, ideas about the problematic field of philosophy of education, the methods and approaches used.